Utility of Rapid Molecular Assays for Detecting Multidrug-Resistant Mycobacterium tuberculosis in Extrapulmonary Samples - Katarzyna Kania; Katarzyna Wójcik; Kamil Drożdż; Karolina Klesiewicz (Diagnostics)
Background: Extrapulmonary tuberculosis (TB) presents significant diagnostic challenges, particularly in the context of multidrug-resistant (MDR) strains. This study assessed the utility of the WHO-recommended rapid molecular assays, originally validated for pulmonary TB, in diagnosing extrapulmonary TB and detecting the MDR Mycobacterium tuberculosis complex (MTBC). Materials and Methods: A total of 6274 clinical samples, including 4891 pulmonary and 1383 extrapulmonary samples, were analyzed between 2019 and 2022 using the BD MAX™ MDR-TB assay (BD MAX), the Xpert® MTB/RIF assay (Xpert MTB/RIF), the Xpert® MTB/XDR assay (Xpert MTB/XDR), FluoroType MTB, and phenotypic drug susceptibility testing (DST). Results: MTBC was detected in 426 samples using BD MAX (376 pulmonary and 50 extrapulmonary), of which 277 were culture-confirmed. Phenotypic testing confirmed 299 positive cultures on Löwenstein–Jensen (LJ) medium and 347 in BD BACTEC™ MGIT™ (BACTEC MGIT) mycobacterial growth indicator tube (BBL) liquid culture. BD MAX showed high sensitivity and specificity for extrapulmonary TB detection (93.1% and 98.4%, respectively). Resistance to isoniazid or rifampicin was identified in 11% of MTBC-positive cases, whereas 3.69% were confirmed as MDR-TB. The molecular assays effectively detected resistance-associated mutations (katG, inhA, and rpoB), with high concordance to phenotypic tests (DST) (κ = 0.69–0.89). Conclusions: This study demonstrates that molecular assays, although validated for pulmonary TB, are also reliable for extrapulmonary TB detection and drug resistance profiling. Their rapid turnaround and robust accuracy support broader implementation in routine diagnostics, especially for challenging extrapulmonary specimens where early detection is critical for targeted therapy.